Dubaï et le sport, image d’une société fracturée - Raphaël Le Magoariec (EchoGéo)
The emirate of Dubaï remains one of the first emirates to have invested in the sport industry during the 1990s. Witnessing the changes of generation within the power of Dubai, integration in this domain also marks the entry of the emirate into a new era by the building of a new image of « global city ». Studying Dubaï through the prism of sport allows us to understand, on the one hand, how the Emirate invests in the field of sport and what its stated goals are, on the other hand, how sport is experienced and practiced in this multi-ethnic society evolving in the emirate. Thus sport brings us a look at, not one, but several Dubaï faces that are superimposed on each other without ever too much rubbing shoulders on the sports ground.